Analysis of Coaches Work Culture Behavior in DIY Province - Trisnar Adi Prabowo; Endang Rini Sukamti; Ardiah Juita; Agus Sulastio; Ni Putu Nita Wijayanti; Ricky Susiono (UNIVERSITAS NEGERI MAKASSAR, 2023)
The purpose of this research is to analyze the coaches work cultural behavior in DIY province in the context of POPNAS 2023 (National Student Sports Week) Indonesia. The importance of this study is to evaluate the trainer's performance during the training periodization. This research uses survey method, its analysis uses quantitative descriptive. The sample of this research is 40 trainers consisting of 15 types of sports, these sports will be competed in the Indonesian POPNAS (National Student Sports Week). The research instrument was a questionnaire in the form of a Google form consisting of 24 statement items. The indicators of the coache work culture behavior are divided into attitudes toward work and behavior on time work. Test the validity of the instrument using Aiken's with a value of 0.898 and Cronbach's Alpha reliability test with a value of 0.791. The results of this study indicate that the cultural behavior of DIY provincial trainers shows the results of